Preparation and study of the Structural, Morphological and Optical properties of pure Tin Oxide Nanoparticle doped with Cu - Duha S. Shaker; Nada K. Abass; Ruqayah A. Ulwall (مجلة بغداد للعلوم)
In this study, pure SnO2 Nanoparticles doped with Cu were synthesized by a chemical precipitation method. Using SnCl2.2H2O, CuCl2.2H2O as raw materials, the materials were annealed at 550°C for 3 hours in order to improve crystallization. The XRD results showed that the samples crystallized in the tetragonal rutile type SnO2 stage. As the average SnO2 crystal size is pure 9nm and varies with the change of Cu doping (0.5%, 1%, 1.5%, 2%, 2.5%, 3%),( 8.35, 8.36, 8.67, 9 ,7, 8.86)nm respectively an increase in crystal size to 2.5% decreases at this rate and that the crystal of SnO2 does not change with the introduction of Cu, and SEM results of the pure and doped confirmed that the particle size is within the range (25-56)nm within the nanosize. UV-Vis studies of reflection spectroscopy revealed that energy of band gap increased with increasing doping ratios (4.33,4.18 ,4.21, 4.21 4.23,4.35) ev For pure and doped with Cu (0.5%, 1%, 1.5%, 2%, 2.5%, 3%) respectively. Results of AFM show roughness rate, SPM and grain size of pure samples doped with Cu where the roughness rate of SnO2 is (3.04, 25,27,16,41.8,23.6,25.2) nm and average diameter is (98.9, 72.56 ,92.91, 88.38, 76.79, 70.94, 71.21) nm for pure and doped with Copper (0.5%, 1%, 1.5%, 2%, 2.5%, 3%) respectively.